1984
DOI: 10.1111/j.1365-2265.1984.tb03471.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Catecholamine, Thyrotrophin, Thyroid Hormone and Prolactin Responses of Normal Subjects to Acute Cold Exposure

Abstract: The responses of circulating catecholamines, TSH, thyroid hormones and prolactin to 30 min of acute cold exposure (4 degrees C) were measured in eight normal volunteers over a 2 h period. There was a rise in circulating noradrenaline, TSH, T4 and T3 levels and a fall in circulating prolactin in the subjects studied, but no change in circulating adrenaline levels nor any alteration in the T4/T3 ratio. The thyroid axis of normal individuals can respond rapidly to acute cold exposure. In addition, the increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 29 publications
5
12
0
Order By: Relevance
“…These results were in agreement with the findings of Weeke and Gundersen [31], O‫ۥ‬Malley et al [23] and Leppäluoto et al [46] who mentioned that testosterone is potentially thermogenic hormone due to its ability to increase the metabolism, but its secretion is suppressed during cold exposure. The decreased testosterone level may be due to that stressors generally induce depression of hypothalamo-pituitary-testis system, mediated by activated hypothalamo-pituitary-adrenocortical system, resulting in fall in plasma LH and testosterone levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results were in agreement with the findings of Weeke and Gundersen [31], O‫ۥ‬Malley et al [23] and Leppäluoto et al [46] who mentioned that testosterone is potentially thermogenic hormone due to its ability to increase the metabolism, but its secretion is suppressed during cold exposure. The decreased testosterone level may be due to that stressors generally induce depression of hypothalamo-pituitary-testis system, mediated by activated hypothalamo-pituitary-adrenocortical system, resulting in fall in plasma LH and testosterone levels.…”
Section: Discussionsupporting
confidence: 83%
“…These results were compatible with the findings of O´Malley [23] who found that exposure to ambient temperature of 4°C for 30-120 minutes increases serum T 3 concentrations. Maurya [24] found that exposure to cold leads to increase of serum T 3 levels.…”
Section: Discussionsupporting
confidence: 83%
“…There was a slight decrease in the concentration of corticosteron following cold exposure compared to 25 C control rats. These findings are comparable with the reports of other cold model studies, for example, rats exposed to 4°C for four hours (2425), and humans exposed to 40C for two hours (22) exhibited elevated serum concentrations of T3, while concentrations of T4 were reduced in both species.…”
Section: B Rat Model Of Cold Stresssupporting
confidence: 82%
“…Acute cold exposure leads to 1) increased heart rate, 2) a rise in both systolic and diastolic blood pressures, and 3) enhancement of cardiovascular responsiveness to ␤-adrenergic stimulation (5,24). Previous studies have shown that cold exposure activates the SNS (47) and increases circulating thyroid hormones (46). There have been several reports on the effect of cold exposure in rats (13,53); however, as far as we know, the effect of cold exposure on the rabbit heart has not been studied.…”
mentioning
confidence: 99%